Climate insurance: Opportunities for improving agricultural risk management in Kenya - Kramer, Berber (International Food Policy Research Institute, 2023)
Climate change represents a major challenge to food systems. It is associated not only with rising average temperatures but also with less predictable weather and changes in humidity, with severe consequences for agricultural production, input markets, aggregation, processing, distribution, and consumption. Negative impacts on food production can raise consumer prices, potentially leading to social unrest and conflict; increased temperatures and changes in humidity require stronger cold chains and improved storage facilities to avoid postharvest damage (de Brauw and Pacillo 2022). This chapter highlights several innovations in climate insurance that were developed and tested in Kenya with the aim of improving smallholder farmers’ ability to manage the production risks associated with climate change.